Perbandingan Kadar Methemoglobin dan Hemoglobin Penduduk Endemis dengan Penduduk Non Endemis Malaria - Astuti, Yoni; Handayani, Rini (Universitas Muhammadiyah Yogyakarta, 2006)
One of the effects of Plasmodium infection and consumption of anti-malaria medicine is the increase of free radicals in the body. Free radicals can attack haemoglobin and change it to met-haemoglobin. The aim of this study was to identify the concentration of met- haemoglobin (as a sign of free radicals) and haemoglobin of individuals living in the malaria- endemic area as compared with individuals living in non-malaria-endemic area.This was a cross sectional study. Subjects of the study were 60 individuals and divided into 2 groups, i.e. Endemic Group (EG) and Non-Endemic Group (NEG). The EG included 30people who were men and women between 20-50years old, had suffered or were suffering from malaria and had been living in endemic area for five years. The NEG included 30 people who were men or women between 20-50 years old and had not suffered from malaria. The blood samples were collected and analysed for met-haemoglobin concentration using Betke method and haemoglobin concentration using cyanmethaemoglobin method.The results showed that the average of met-haemoglobin concentration of NEG was (2,188 ± 0,662)% and EG was (3,728 ± 0,492)%, while the average of haemoglobin concentration of NEG was (14, 183 ± 2,593)g% and EG was (10,376 ± l,447)g%. This demonstrated that the concentration of haemoglobin between NEG and EG was different significantly (p 0,05).Salah satu akibat terinfeksi plasmodium dan dampak mengkonsumsi obat - obatan menyebabkan meningkatnya radikal bebas. Radikal bebas dapat menyerang haemoglobin sehingga menj adi methemoglobin. Tujuan penelitian ini adalah untuk mengetahui kadar methemoglobin (sebagai marker radikal bebas) dan hemoglobin penduduk endemis malaria dibandingkan dengan kadar methemoglobin penduduk non endemis.Penelitian ini adalah penelitian cross sectional dengan subyek sebanyak 60 orang dibagi menjadi 2 kelompok. Kelompok endemik malaria sebanyak 30 orang yaitu laki-laki dan wanita berumur20-50 tahun yang pernah atau sedang menderita malaria dan telah tinggal di daerah endemis selama minimal lima tahun. Kelompok non endemik malaria sebanyak 30 orang yaitu laki-laki dan wanita berusia 20-50 tahun yang tidak pemah menderita penyakit malaria. Subyek diambil darahnya dan selanjutnya dilakukan analisis kadar methemoglobin menurut metode Betke, dan diukur kadar hemoglobin dengan metode cyanmethemoglobin.Hasil penelitian menunjukkan bahwa persentase methemoglobin KNE (Kelompok Non Endemis) adalah (2,188 ± 0,662) % Hb dan KE (Kelompok Endemis) adalah (3,728 ± 0,492) % Hb. .Hasil penelitian kadar hemoglobin menunjukkan bahwa persentase hemoglobin KNE adalah (14,183 ± 2,593) g % dan KE adalah (10,376 ± 1,447) g %. Hal itu memperlihatkan adanya perbedaan signfikan antara KNE dan KE (p 0,05).